PENGARUH TINGKATKAN PENDIDIKAN ORANG TUA TERHADAP MOTIVASI BELAJAR SISWA DI MI AL HIKMAH - Ahmad Yunus Wahyu Saputra (UNISAN JURNAL, 2024)
This research examines parental guidance in fostering moral and spiritual development in children. In this research, the research method used is qualitative. Qualitative methods are used to understand phenomena regarding behavior, perceptions, motivations, actions, etc. experienced by research subjects holistically. Research findings show the reality of parental guidance in the development of children's spiritual morals at MI AL Hikmah including variations in the level of parental involvement. Some parents show apathy in providing tutoring, because they are busy with household work. However, they often still use their free time to surf the internet via their gadgets. But on the other hand, there are also parents who are actively involved in guiding their children. The implementation of parental guidance in developing children's spiritual morals at MI AL Hikmah shows that parents who are directly involved in guiding their children have tried their best according to the existing stages. However, there are still several aspects that need to be considered in implementing the process to ensure its effectiveness.